Knowledge Regarding Adverse Effects Of tobacco Smoking Among The Schizophrenia Patients - Subhra Sarkar; Arunjyoti Baruah; Bineeta Nath (Indian Journal of Psychiatric Nursing)
Heavier tobacco smoking pattern, in spite of its detrimental consequences is common among the schizophrenia patients in India as it is in the rest of world. But very limited studies have been conducted in north-east of India to find the knowledge level among the schizophrenia patients regarding the adverse effects of tobacco smoking, which is again limited in rest of India and outside India. Therefore, the study was conducted with the aim of assessing the knowledge regarding adverse effects of tobacco smoking among the schizophrenia patients. Materials and methods: A descriptive research design was adopted to conduct the study at the out-patient department of LGBRIMH, Tezpur. A sample of 30 schizophrenia patients diagnosed as per ICD-10 criteria, were selected by using a purposive sampling technique. The data was collected by using a self-structured questionnaire and was analyzed by descriptive and inferential statistics. Results: Findings revealed that among the schizophrenia patients, majority (80.0%, n=24) were having an increased knowledge score regarding the adverse effects of smoking and there was a significant association present (χ2=5.000, P=0.025) between the knowledge score and the level of education of the participants. Conclusion: The study results shows that motivation enhancement among the schizophrenia patients will be very important for their self motivated involvement for the avoidance of this negative health related behaviour which has some detrimental adverse effects particularly on their present health condition.